Deep change : cases and commentary on reform in high stakes states - Ponder, Gerald; Strahan, David B.; Lieberman, Ann; Fullan, Michael (Emerald Publishing Limited : Information Age Publishing, 2005)
This book presents cases of schools (Part One) and programs at the district level and beyond (Part Two) in which reform, while driven by high-stakes accountability, became larger and deeper through data-driven dialogue, culture change, organizational learning, and other elements of high performing cultures. Commentaries on cross-case patterns by Ann Lieberman and Michael Fullan and a chapter on "now what?" first steps provide implications for initiating deep change that results in improved student learning outcomes even in challenging activity settings.
Keywords: School improvement programs -- United States -- Case studies.; Educational change -- United States -- Case studies.; Educational accountability -- United States -- Case studies.; Academic achievement -- United States -- Case studies.; elektronické knihy; Case studies.; Education -- Educational Policy & Reform -- General.; Educational administration and organization.; Educational strategies and policy.; electronic books